THE ROLE OF THE CIREBON CITY DPRD IN REALIZING POLICIES BASED ON COMMUNITY ASPIRATIONS - Trully, Visia Nurmalita; Fitriliya, Mariska; Ramadani, Intan Fitria; Harmono, Harmono (Jurnal Abdisci, 2025)
Abstract: Background. This article explains the city's Regional People's Representative Council (DPRD), which has a strategic role in realizing policies based on community aspirations, as a representation of the people. Aims. The DPRD is in charge of legislation, budgeting, and supervision of local governments. This research aims to describe the extent of the city DPRD's role in absorbing, processing, and implementing the community's aspirations into public policies that have a real impact. Methods. This study used a qualitative descriptive approach, with data collection techniques involving literature studies, interviews, and observations. Result. The study's results show that the city DPRD has formal mechanisms, such as recess, hearings, and deliberative forums, to absorb the community's aspirations. However, the challenges faced include uncertainty of public participation, the dominance of political pressure, and budget and resource constraints. Conclusion. To increase the effectiveness of the DPRD's role in realizing policies based on people's aspirations, transparency, accountability, and stronger communication between the legislature and the public are necessary. Implementation. Thus, the resulting policies can be more relevant and in the public interest.